A QFD as decision model for re-evaluating seaport criteria - Mustafa Abd Elhafez; Sameh Rashad; Tamer Said Riad (Maritime Research and Technology)
Maritime container and cargo shipping are profitable pursuits for shippers and shipping lines associations to transport various cargo types among different seaports and harbors. Locating and selecting the most appropriate ports and routes from several alternatives are referred to be a complicated Multiple Criteria Decision Making (MCDM) issue since it demands the multiple factors. Ports become an essential element of global or regional supply chains network or even a distribution center of a region, ports efficiency must be reconsidered as ports logistics efficiency to be compatible with the new trends in the maritime industry. Since the shipping line is integrated with the global supply chain and controlling the port and route choices the port selection criteria changed and are different from traditional selection factors, thus it obvious now the need to re-ranking the various ports selection criteria to be compatible with the new selection maritime transportation era. port selection criteria in the shipping route based on the Quality Function Deployment (QFD) concept and statistical research findings, considering the integration management of maritime shipping lines into global supply chains, the most noteworthy determining when shipping lines select the port of call on a single route, port Geographical Location is the second most significant selection parameter, behind port effectiveness and IT Ability. The third issue to take into consideration is the port dues and terminal handling charges. This paper illustrates applying the quality function deployment (QFD) technique as deciction making model in the maritime transportation , beside adapt it as tool to rerank and re-assesset the port selection criteria weights of importance that reflect on the shipping routs as result of integration the shiping line and container shipper companies in the global supply chain network